2022
DOI: 10.1002/pd.6196
|View full text |Cite
|
Sign up to set email alerts
|

Use of fetal tele‐echo at small regional hospitals increases the rate of prenatal diagnosis of congenital heart disease

Abstract: Background:To improve the rate of prenatal diagnosis of Congenital heart disease

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 20 publications
0
10
0
1
Order By: Relevance
“…32 A testable intervention is telemedicine, which has applications in remote ultrasonography, where a local ultrasonographer performs real-time fetal echocardiograms with the virtual guidance of a pediatric cardiologist, 33 as well as remote counseling for CHDs. 34,35 Telemedicine has demonstrated success in increasing prenatal diagnosis rates for states with a single CHD surgical center. 36,37 Conversely, telemedicine could exacerbate disparities due to a patient's lack of broadband Internet access or insufficient privacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 A testable intervention is telemedicine, which has applications in remote ultrasonography, where a local ultrasonographer performs real-time fetal echocardiograms with the virtual guidance of a pediatric cardiologist, 33 as well as remote counseling for CHDs. 34,35 Telemedicine has demonstrated success in increasing prenatal diagnosis rates for states with a single CHD surgical center. 36,37 Conversely, telemedicine could exacerbate disparities due to a patient's lack of broadband Internet access or insufficient privacy.…”
Section: Discussionmentioning
confidence: 99%
“…Finding solutions for both barriers first requires understanding whether there is (1) a sufficient supply and (2) an efficient distribution of maternal‐fetal medicine subspecialists and fetal cardiologists to meet demand 32 . A testable intervention is telemedicine, which has applications in remote ultrasonography, where a local ultrasonographer performs real‐time fetal echocardiograms with the virtual guidance of a pediatric cardiologist, 33 as well as remote counseling for CHDs 34,35 . Telemedicine has demonstrated success in increasing prenatal diagnosis rates for states with a single CHD surgical center 36,37 .…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound can be performed in many clinical settings; however, access to clinical settings with advanced imaging technology and expertise is often limited to large urban settings. 25,26 Therefore, the use of telehealth provides the opportunity to perform an ultrasound at a remote location and transmit those images either in real-time or asynchronously for review and consultation with a specialist. 26,27 This is well illustrated by a study using telehealth to expand fetal echo coverage that found that prenatal detection of congenital heart disease increased from 13.8% to 37.9%.…”
Section: Delivery Of Services By Non-genetics Providersmentioning
confidence: 99%
“…26,27 This is well illustrated by a study using telehealth to expand fetal echo coverage that found that prenatal detection of congenital heart disease increased from 13.8% to 37.9%. 25 Another study from the Antenatal and Neonatal Guidelines, Education and Learning System, described leveraging a current telemedicine network to bring maternal-fetal medicine and urology consults to patients with a fetal diagnosis of urologic anomalies in rural areas. 28 ADAMS ET AL.…”
Section: Delivery Of Services By Non-genetics Providersmentioning
confidence: 99%
“…Respecto a la utilidad en las cardiopatías congénitas, la implementación de un sistema de teleultrasonido en hospitales regionales pequeños mejora la tasa de detección de anomalías cardíacas (13,8% antes frente a 39,7% luego de su implementación; p < 0,01) 11 .…”
Section: Telemedicina En Diagnóstico Prenatalunclassified